The impact of nitrogen deposition on nitrogen metabolism in ryegrass lawn with different soil nutrient levels - Xiu-Lin Song; Zi-Jie Wang; Xian-Wei Yin; Yan-Lin Sun; Dong-Jin Jang; Soon-Kwan Hong (Scientific Reports)
Abstract Nitrogen deposition is a crucial factor in global change, which is widespread across various regions globally. It has drawn extensive attention due to its direct modification of soil nitrogen retention and nitrogen species distribution, thereby influencing nitrogen metabolism across entire ecosystems. Previous studies on its influence on nitrogen metabolism have not reached a consensus. In an urban ryegrass lawn mesocosm experiment, we set two levels of nitrogen deposition and soil nutrients respectively, aiming to study the impacts of these factors on the N-cycling process through metagenomic analysis. The results demonstrated nitrogen deposition increased nitrification, nitrogen fixation, denitrification, and dissimilatory nitrate reduction, but decreased assimilatory nitrate reduction in the nitrogen metabolism process by changing soil nitrogen availability and the abundance of N-cycling functional genes in the soil microbial community. The soil nutrient levels exhibited effects opposite to those of nitrogen deposition, negatively impacting nitrification, denitrification, and nitrogen fixation in the nitrogen metabolism process. This work further elucidates the impacts of nitrogen deposition on the ecological functions of the ryegrass lawn with different soil nutrient levels, and predicts the potential impacts of intensified nitrogen deposition on these ecological functions. It provides valuable theoretical support for understanding and evaluating complex ecological interactions.